Growth of Higher Education and its Determining Factors in Cambodia - Vuth, Mr. Doung; Dash, Dr. Tapas R. (Advances in Social Sciences Research Journal, 2017)
The study analyzes the growth of higher education in Cambodia by considering indicators like number of institutions, number of enrolment, number of teachers and expenditure on education. Further, it examines the factors determining the growth of higher education (enrolment) in the country. The results of the study show phenomenal growth of higher education in the country over the period of study. The opening of new universities, institutes and branches of institutes in the country was due to the increasing demand for higher education by a growing knowledge-seekers, the commitment of the government to provide greater access to higher education and incoming of private players into the education sector. It is also revealed from the study that number of students passed out from high schools and per capita GDP at current prices had significant positive impact on the enrolment of students at higher education level in the country. Thus, the findings have implications for education service providers, planners, policy makers, non-government organizations, donors and other stakeholders in ensuring provision of educational facilities to meet the growing demand for higher education in Cambodia.